Rancang Bangun Website Pencatatan Pelanggaran Siswa untuk Evaluasi Disiplin di Sekolah Menengah Kejuruan - Akmal, Nabil Faisal; Muhammad, Taofik; Habibie, Alfadl (Journal Digital Technology Trend, 2026)
The advancement of information technology has encouraged various innovations in the education sector, including web-based student violation recording systems. This study designed and developed a web-based platform to support the recording of student violations at SMK Muhammadiyah Tasikmalaya, employing the Research and Development (R&D) method alongside the ADDIE model — Analysis, Design, Development, Implementation, and Evaluation. Built on the Laravel framework, the system provides structured features for managing violation categories and types, recording individual student violations, and generating discipline evaluation reports, enabling teachers to monitor and evaluate student conduct more accurately. Two evaluation approaches were applied: the TELOS framework (Technical, Economic, Legal, Operational, Schedule) to assess overall feasibility, and the Black Box method to verify functional performance. Results across all five TELOS dimensions placed the system in the "highly feasible" category, with an aggregate score of 86.45. These findings confirm that the system is ready for institutional deployment as a reliable, technology-based tool for student discipline management.